Application of chemography for evaluating the workability of hard alloy cutting plates - Аleхandеr Salenko; Mykhailo Elizarov; Viktor Shchetinin; M. A. Al-Kuraan Tarek; Sergiy Klymenko (Mechanics and Advanced Technologies)
Abstract: An approach to assessing the performance of carbide cutting inserts based on fixing changes in the defectiveness of its structure is proposed. The assessment is based on the phenomenon of activation of inhomogeneous chemical processes at extremely low concentrations of substances that occur in places of excessive surface activity in the structure of the material. The effect is determined by the initial imperfection of the structure of the surface layer of the material and the increase in the defectiveness of the carbide material under the influence of thermobaric loading during the operation of the tool. It is proposed to use the black index of the chemographic image of the studied object as a criterion for the array of structural defects, the value of which indicates the level of structural violations and internal defects in the material.